Umbilicated Hairy Auricular Mass Mimicking Accessory Tragus - Choi, Jeong Hwan (J Audiol Otol, 2020)
Trichofolliculoma (TF) is a follicular hamartoma in which hairs protruding out of single orifice. To the best of my knowledge, only two auricular TF has been reported in the English literature. Moreover, clinically TF have been described to mimic malignancy. I present a case of an adult female with mass at the intertragal notch of the left auricle for several years. The clinical diagnosis was thought to be epidermoid cyst, accessory tragus, and other benign skin adnexal tumor. To prevent recurrence, the wide local excision of the mass was performed. The final diagnosis of TF was made. No recurrence was noted during the follow-up of 1 year. It is important for otologists to be familiar with the clinical and pathologic characterization of TF, to make the correct diagnosis.